An Analysis Finding Nemo Movie to Explore Student Perception and Vocabulary Acquisition - M. Junaidi Marzuki; Andri Suherman; Elin Maulida Apriani; Siti Maysuroh (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
This study investigates students’ perceptions of the animated film Finding Nemo as a medium for learning English vocabulary and explores how it facilitates vocabulary acquisition in authentic and engaging contexts. Employing a descriptive qualitative approach, the study involved 35 second-semester students of the English Education Study Program at Hamzanwadi University. Data were gathered through open-ended questionnaires and semi-structured interviews, and analyzed thematically to identify patterns emerging from participants’ responses. The findings indicate that students generally have positive perceptions toward using Finding Nemo in vocabulary learning. They reported acquiring both concrete and abstract vocabulary through contextual exposure in the film’s dialogues and visual storytelling. The combination of audio, visual, and emotional elements enhanced comprehension and long-term retention. Moreover, students expressed that learning through the film was more enjoyable and motivating compared to traditional methods, as it fostered a relaxed and interactive learning environment. These results suggest that animated films such as Finding Nemo not only enrich students’ vocabulary but also promote positive attitudes and motivation toward learning English.